Karya Nyata Karang Taruna: Pengabdian Berkelanjutan Untuk Mengukir Peningkatan Kualitas Hidup Di Desa Sungon - Achmad Tanzilur Rozzak; Wahyu Eko Pujianto (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Karang Taruna's Real Work Program in Sungon Village is a sustainable effort to improve the quality of life of the community. This research aims to explain the problems faced, the program objectives, the methods used, and the results that have been achieved. Karang Taruna Sungon has succeeded in launching superior programs in local economic empowerment, education, public health and sustainable environmental projects. Small business training and preventive health campaigns are the main focus, implemented through active member participation in a spirit of mutual cooperation. The community's positive response to the Karang Taruna initiative created a climate of mutual listening and support, even though they faced limited resources. Program sustainability is maintained through ongoing planning, member capacity development, and support from external partners and donor agencies. Despite the challenges, Karang Taruna was able to overcome most of them, gaining important lessons about adapting to local changes and community participation. The implementation of the program has had a significant impact on Sungon Village, including increasing living standards, reducing poverty levels, and higher local economic participation. Close collaboration with local government, non-government organizations and the private sector is the key to success in supporting the overall village development vision.